PERLINDUNGAN HUKUM PELAKU USAHA LOKAL DALAM PASCA PERATURAN PRESIDEN NOMOR 12 TAHUN 2021 - SULAIMAN SULAIMAN; AKBAR TAUFIK AMRULLAH; REYHAN DYO ZACHARY (Universitas Borneo Tarakan, 2025)
This research aims to analyze the effectiveness of legal protection for local business actors in government procurement of goods and services following the implementation of Presidential Regulation No. 12 of 2021. The research method employs a normative juridical approach with descriptive-analytical qualitative analysis techniques on procurement regulations and their implementation. Data collection techniques were conducted through comprehensive literature studies on primary, secondary, and tertiary legal materials relevant to legal protection for local business actors. Research findings indicate a paradigm transformation from passive to active-affirmative approaches through layered protection mechanisms including price preferences up to 15% for domestic products, administrative procedure simplification, digital information access facilitation, and strengthened risk-based supervision systems. Implementation of this regulation successfully increased local business participation with a 35% increase in contract value and creation of 150,000 new jobs within two years of implementation. However, challenges remain in inter-agency coordination with implementation variance reaching 40%, limited human resource capacity, and suboptimal integration of supervision information systems. The research concludes the necessity for optimization strategies through strengthened real-time monitoring, integrated digital platform development, and systematic capacity building programs to ensure sustainable legal protection effectiveness